Mitigating disease risk in an endangered pinniped: early hookworm elimination optimizes the growth and health of Australian sea lion pups - Lindsay, Scott A.; Fulham, Mariel; Caraguel, Charles G. B.; Gray, Rachael (Frontiers in Veterinary Science, 2023)
The Australian sea lion (Neophoca cinerea) experiences high pup mortality of seasonally alternating severity, partly attributed to endemic hookworm (Uncinaria sanguinis) infection. To further explore health outcomes of early hookworm elimination, a treatment trial was conducted at Seal Bay Conservation Park, South Australia, over consecutive lower and higher mortality breeding seasons (2019, 19.2%; 2020–1; 28.9%). Pups (n = 322) were stratified into two age cohorts (median 14 d and 24 d recruitment ages) and randomly assigned to treated (topical ivermectin 500 μg/kg) or control (untreated) groups. A younger prepatent cohort <14 d old (median 10 d) was identified a posteriori. A seasonally independent growth benefit resulted from hookworm elimination across all age cohorts. The greatest relative improvements (bodyweight + 34.2%, standard length + 42.1%; p ≤ 0.001) occurred in the month post-treatment, in the youngest prepatent cohort. A significant benefit of lesser magnitude (bodyweight + 8.6–11.6%, standard length + 9.5–18.4%; p ≤ 0.033) persisted up to 3 months across all age cohorts – greatest in the youngest pups. Treatment resulted in immediate improvement in hematological measures of health – decreased anemia and inflammation severity (p ≤ 0.012). These results enhance our understanding of host–parasite–environment interactions within the context of hematological ontogenesis, confirm the seasonally independent benefits of hookworm disease intervention, and further inform conservation recommendations for this endangered species.